Thaxtomin production and pathogenic diversity in Streptomyces species causing common scab in potato - SINGHAI, PRINCE K.; SARMA, B.K.; SRIVASTAVA*, J.S. (Indian Phytopathology, 2011)
A study was carried out to compare scab index and scab incidence of sixteen Streptomyces strains isolated fromscabby potato tubers of eight varieties collected from different regions of India. All the 16 strains found pathogenic in pot test,whereas only 13 showed pathogenic nature in the tuber slice test. Depending on symptom development, the strains werecategorized as highly, moderately and least pathogenic, based on their scab index and scab incidence. Detection andquantification of thaxtomin A was also carried out using TLC and HPLC. It was found that out of 16 strains, 7 showed presenceof thaxtomin A in TLC, produced in different quantities in oat meal broth medium. Out of those 7 strains, 6 strains were highlypathogenic while only one showed moderate pathogenicity. This is one of the preliminary studies conducted on Indianisolates of Streptomyces causing common scab of potato.